2021
DOI: 10.1016/j.ejca.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobin G/total antibody testing for SARS-CoV-2: A prospective cohort study of ambulatory patients and health care workers in two Belgian oncology units comparing three commercial tests

Abstract: Background Coronavirus disease (COVID-19) is interfering heavily with the screening, diagnosis and treatment of cancer patients. Better knowledge of the seroprevalence and immune response after Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection in this population is important to manage them safely during the pandemic. Methods 922 cancer patients, 100 non-cancer patients and 94 healthcare workers (HCW) attending the Multidisciplinary Oncology Unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(57 reference statements)
1
14
0
1
Order By: Relevance
“… 10 , 11 , 12 , 13 In addition, low or even absent antibody response after SARS-CoV-2 infection has been reported, particularly in patients with advanced cancer and B-cell hematological malignancies. 7 , 8 Emerging evidence shows that SARS-CoV-2 vaccination efficacy might be lower in elderly and immunocompromised. 22 , 23 Our prospective interventional trial demonstrated an acceptable safety profile of the BNT162b2 mRNA COVID-19 vaccine with a reduced and delayed antibody response in both solid and hematological cancer patients receiving anti-neoplastic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 , 12 , 13 In addition, low or even absent antibody response after SARS-CoV-2 infection has been reported, particularly in patients with advanced cancer and B-cell hematological malignancies. 7 , 8 Emerging evidence shows that SARS-CoV-2 vaccination efficacy might be lower in elderly and immunocompromised. 22 , 23 Our prospective interventional trial demonstrated an acceptable safety profile of the BNT162b2 mRNA COVID-19 vaccine with a reduced and delayed antibody response in both solid and hematological cancer patients receiving anti-neoplastic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that SARS-CoV-2 exposed patients with hematological malignancies display heterogeneous humoral immune response, an exhausted T-cell phenotype and a high prevalence of prolonged viral shedding. 5 , 6 , 7 , 8 Although patients with solid tumors often develop immune response signatures similar to those of non-cancer patients 9 , they remain at increased risk of severe COVID-19. 10 , 11 , 12 , 13 Hence, according to various oncological associations, high priority for vaccination should be given to these patients, regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is encouraged in these immunosuppressed patient groups, although it is possible that the immune responses will be less robust, as has been seen in response to natural infection. 152 153 Indeed, early studies are showing comparable safety, but reduced immunogenicity has been observed for these populations, including patients with HM, 154–156 SOTRs, 157 and those with rheumatological diseases. 158 159 To achieve comparable vaccine efficacy, further strategies employing altered vaccine schedules, doses, or adjustment to immunosuppression during vaccination might be needed, and should be accomplished only in the context of a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity and specificity of these tests was at least 98% in a head-to-head comparison study, 12 with some divergent results in seroprevalence studies on cancer patients. 13 Continuous variables are expressed as median, minimum, and maximum values. Categorical variables are presented as frequencies and percentages.…”
Section: Methodsmentioning
confidence: 99%